THE EFFECT OF COMPENSATION, CAREER DEVELOPMENT AND WORK EXPENSES ON TURNOVER INTENTION AT PT SUKSES KELOLA PERSADA - Rahma Dini, Silvia; Charles Bohlen Purba (Dinasti Publisher, 2020)
This study aims to measure the effect of compensation, career development, and workload on turnover intention of PT. Successfully Manage Persada or Trade Mall Mangga Dua Square. This research is quantitative in nature. The population is all employees of PT. Success Manage Persada. The sampling technique was random sampling with a sample of 114 employees. The research data were analyzed using multiple linear regression using the SPSS 25 test tool. The results of the t-test for compensation and career development variables partially had a significant negative effect, and workload partially had a significant positive effect on turnover intention. The results of the F-test show that the Sig. ie 0.000 and less than 0.05. This indicates that the variables of Compensation, Career Development, and Workload together have a significant effect on Turnover Intention (H4 accepted). The results of the normality test showed that 0.96, which means greater than 0.05. This means that the residual data is normally distributed. Suggestions for further research are to include other factors that have a strong influence with Turnover Intention.